How sustainable transportation can utilize climate change technologies to mitigate climate change - Din, Ashraf Ud; Ur Rahman, Imran.; Vega Muñoz, Alejandro.; Elahi, Ehsan; Salazar Sepúlveda, Guido Rolando.; Contreras Barraza, Nicolás.; Alhrahsheh, Rakan Radi (MDPI, 2023)
The build-up of greenhouse gases (GHGs) is causing warmness in the Earth’s atmosphere, resulting in climate change. The transport sector is one of the active causes of GHG emissions and it is imperative to use sustainable transport sources to control climate change. There is a measure that aims to encourage citizens to stop using their own vehicles as their choice of transport and instead opt for joint sustainable mobility during traveling. In this study, a quantitative research method was used and data were collected from a sample of 410 respondents through a questionnaire. Furthermore, this study also took a simulation-based (n = 10,000) sample size of electric rail vehicle data. The data were analyzed using structural equation modelling. The results revealed that sustainable transportation, climate change technologies, and electric rail vehicles reduce climate change in the ecoregions of China. We conclude that sustainable transportation policies could be formulated and implemented to reduce climate change. In response to the research results, it is recommended that, since climate change is a multi-level governance issue, the outdated pyramidal transport industry models must be shifted to a sustainable transportation system model.
Keywords: Reduced carbon emissions; Sustentabilidad; Transporte; Cambios climáticos